The Role of Digital Technology in Optimizing the Agrocomplex Value Chain - Pratiningrum, Marbella (Professorline, 2025)
Digital technology has transformative potential in optimizing agrocomplex value chains, but its implementation in developing countries such as Indonesia still faces various challenges. This study analyzes the role of digital technology in optimizing agrocomplex value chains with a focus on implementation in Indonesia. Through a comprehensive analysis of various cases of digital technology implementation in the agricultural sector, this study identifies significant benefits including increased productivity by up to 27.3%, reduced production costs by 18.7%, and efficient use of resources. The analysis also reveals a gap in technology adoption between large and small-scale farmers, as well as the importance of a supporting ecosystem that includes digital infrastructure, capacity development, and conducive policies. The inclusive partnership model and ecosystem-based approach have proven effective in increasing the adoption rate and benefits of digital technology. This study provides a comprehensive framework for implementing digital technology in agrocomplex value chains that considers technological, socio-economic, and environmental sustainability aspects. The implications of this study are relevant for developing policies and strategies for digital transformation in the agricultural sector in Indonesia and other developing countries.